Coaching is key to SME success. Issue 3 (1st April 2014) - Bell, Gareth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the paper is to provide an interview with Peter Boolkah. Design/methodology/approach – The paper discusses some of the current issues within the coaching industry. Findings – Boolkah answers questions on coaching philosophy, what attributes make a successful coach and how a business can make the most of a coach's expertise. Practical implications – Provides insight and advice from a leading industry professional.